DETERMINATION OF STOPPING DISTANCE OF UNPOWERED ROLLING STOCK BY METHOD OF SEQUENTIAL BRAKING - Reidemeister, O. H.; Shaposhnyk, V. Yu. (Science and Transport Progress, 2015)
Purpose. In the paper it is necessary to estimate the determination accuracy of a car stopping distance during the test by the method of sequential braking. The method of sequential braking is applied for experimental evaluation of the stopping distances. Unlike the abandonment method when a sample car is disconnected from the tractive connection and they record the stopping distance of a single car from the moment of uncoupling to the moment of stop, the method of sequential braking involves stopping distance measurement of the tractive connection, the integrity of which in the course of the test is not affected, but its set (locomotive, locomotive with the track test car or with a sample car) at the different stages of the test is changed. Direct measuring of the stopping distance of a sample car is not possible using this way, it requires calculating of the stopping distance values of the tractive connection. This adversely affects the accuracy of the result, but it can increase the safety level of the test. Methodology. To evaluate the accuracy researches have conducted the numerical experiment, which simulated experimental processing of stopping distance values. An error was found by giving disturbance of basic data (stopping distance of tractive connection of different configuration) and analyzing the resulted scatter of readings (stopping distance of a single car). Findings. The study proved: 1) the relative error of car stopping distances value, with relative error of basic data 1%, made 3.3-19.7% (depending on the tractive connection variant). 2) the proposed ways of error reduction (without track test car, less-weighed-locomotive use) allowed declining the error to 2.15-5.1%. Originality. The methodology of error estimation of car stopping distances determination under tests by the method of sequential braking was proposed. Practical value. Work results make it possible to replace the running brake tests by the abandonment method, under which the integrity of tractive connections is broken, with safer testing by the method of sequential braking, providing the level of result accuracy of 2-5%.